Councillor Clubs in Communes in Poland and France - Augustyniak, Monika Ewa (Review of European and Comparative Law, 2021)
The article presents the legal status of councillor clubs in Poland and in France. It discusses establishment and functioning of clubs that are usually created on the basis of political criteria, in the light of a councillor’s free mandate and social control. It presents elements of club’s financing and possibility to express opinions by minority clubs in a council. The analysis of the legal status of councillor clubs leads to conclusions and determination of the direction of changes in the scope of the research concerned. The legal status of councillor clubs corresponds to the issue of quality of democratisations of a self-governing authority. Therefore, specification of premises determining organisation and operation of councillor clubs in a municipal council is a significant regime-related issue. The problems related to functioning of the councillor clubs in the Polish and French legal orders is currently a challenge for contemporary local self-government.